2022
DOI: 10.3390/plants11091213
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Betaine and β-Aminobutyric Acid Mitigate the Detrimental Effects of Heat Stress on Chinese Cabbage (Brassica rapa L. ssp. pekinensis) Seedlings with Improved Photosynthetic Performance and Antioxidant System

Abstract: Heat stress is one of the major abiotic factors that limit the growth, development, and productivity of plants. Both glycine betaine (GB) and β-aminobutyric acid (BABA) have received considerable attention due to their roles in stimulating tolerance to diverse abiotic stresses. In order to understand how GB and BABA biostimulants alleviate heat stress in a cool-weather Chinese cabbage (Brassica rapa L. ssp. pekinensis) plant, we investigated the GB- and BABA-primed heat-stressed plants in terms of their morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The substantial increase in stachydrine as a result of D and H treatments represents the first observation that stachydrine is associated with the defense against a fungal pathogen. Upon P852 treatment, the relative content of betaine was increased, which is a cytoplasm-localized substance that is capable of increasing the activities of antioxidant enzymes and rapidly scavenging the ROS produced upon fungal attack [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The substantial increase in stachydrine as a result of D and H treatments represents the first observation that stachydrine is associated with the defense against a fungal pathogen. Upon P852 treatment, the relative content of betaine was increased, which is a cytoplasm-localized substance that is capable of increasing the activities of antioxidant enzymes and rapidly scavenging the ROS produced upon fungal attack [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, plant adaptation to heat stress would be dependent on simultaneous multiple responses associated with changes in physiological, biochemical, and molecular processes as a result of well-coordinated interplays of many different multigenic protective pathways and complex regulatory networks. In our previous study, we showed that GB, when exogenously applied, enhanced the thermotolerance of Chinese cabbage through the higher levels of photosynthesis, osmoprotection, and antioxidant enzyme activities [ 41 ]. This finding is further corroborated by the present study showing that GB pre-treatment increased the contents of RWC and ATP along with the decreased level of superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…As a cool-weather crop, B. rapa is susceptible to heat, especially in early August in the high temperature (over 30 °C) of the Yangtze River area in China [ 40 ]. Previously we reported that GB priming substantially enhanced the thermotolerance of B. rapa seedlings by promoting photosynthesis performance, osmoprotection, and antioxidant enzyme activity [ 41 ]. To further gain an insight into the underlying molecular mechanisms of GB-primed thermotolerance, we investigated the genome-wide gene expression profiles of B. rapa seedlings treated with GB before heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis and Lactuca sativa plants treated with ethanol exhibit enhanced tolerance to heat stress, which is associated with the stimulation of response to unfolded proteins ( Matsui et al., 2022 ). Heat stress is also modulated following treatment with β-aminobutyric acid (BABA) in Arabidopsis and Brassica rapa , through the induction of heat shock proteins and the improvement of photosynthesis performance and antioxidant systems, respectively ( Zimmerli et al., 2008 ; Quan et al., 2022 ). Although chemical priming is an effective strategy of alleviating damage caused by environmental stress in plants without genetic engineering, little is known about the chemical compounds that enhance tolerance to oxidative stress in plants.…”
Section: Introductionmentioning
confidence: 99%